Mari of Bashkortostan in 1970-2010: Demographic and Linguistic Aspects of Ethnic Development - F. G. Safin; K. O. Sirazetdinov (Научный диалог, 2020)
The issues of ethnodemographic and ethnolinguistic development of the Mari population in Bashkortostan are considered. Particular attention is paid to the characteristics of the ethno-demographic situation in the regions of the country with a significant number of the Mari ethnic group. The results of a comparative analysis of the natural reproduction of the Mari in comparison with other ethnic groups in the republic are presented. The question is raised about the ethnolinguistic identity of the Mari population, which, according to census data, is losing its national language. The novelty of the study is seen in the fact that for the first time an analysis of the demographic and linguistic aspects of the development of the Mari population in the regions of the Ural-Volga region was carried out. The relevance of the study is due to the fact that the issue of demographic development of the peoples of Russia at the present stage is becoming not only a social, but also a political and strategic problem. The authors elaborate on the results of interethnic interaction of the Maris in the zone of ethnocultural contacts. It is proved that, despite the high birth rate, the demographic development of the Maris has a negative balance. A review of the ethno-linguistic development of the Mari population is carried out taking into account the administrative-territorial division. It is concluded that the emerging trend of urbanization of the Mari negatively affects the preservation of the native Mari language.